Case report of E.T.—The Extra-Terrestrial. (18th December 2012) - Scott, Gregory; Presswood, Edward
Abstract : Gregory Scott and Edward Presswood present the intriguing case of ET and provide advice for those who have a medical close encounter with an extraterrestrial